A concordância em expressões nominais coordenadas com apenas um determinante - Colaço, Madalena; Gramacho, Carolina (Revista da Associação Portuguesa de Linguística, 2018)
This paper provides a corpus-based study of agreement in coordinate nominal expressions with only one determiner in European Portuguese. The data presented in our previous work attested the use of these expressions in written discourse, contradicting what is stated in some grammars. A distinction between two constructions is established: (a) those in which the coordinate nominal expression refers only one entity, which are commonly considered acceptable in grammatical descriptions; (b) those in which nouns are used to refer distinct entities, which are often considered anomalous or even ungrammatical. We focus especially on structures involving a singular determiner and two singular nouns and observe the type of agreement triggered by the nominal expression in each case: singular agreement versus plural agreement. Our proposal is based on the idea that these constructions correspond to structures that are distinct from the beginning of syntactic derivation, differing with respect to the coordinated categories (NP versus DP) and the number of determiners selected for the numeration (only one determiner from the beginning versus two determiners in the beginning and post-syntactic deletion of the second determiner), and provides a simple account of internal and external agreement facts.